2017
DOI: 10.1038/s41598-017-06071-9
|View full text |Cite|
|
Sign up to set email alerts
|

Balance training improves memory and spatial cognition in healthy adults

Abstract: Physical exercise has been shown to improve cognitive functions. However, it is still unknown which type of exercise affects cognition. In the present study, we tested the hypothesis that a demanding balance training program improves memory and spatial cognition. Forty healthy participants aged 19–65 years were randomly assigned to either a balance or relaxation training intervention. Each group exercised twice a week for a total of 12 weeks. Pre- and posttests assessed balance performance, cardiorespiratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
70
2
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 43 publications
(45 reference statements)
5
70
2
5
Order By: Relevance
“…Budde, Voelcker‐Rehage, Pietrabyk‐Kendizorra, Ribeiro, and Tidow (), for example, found better attentional performance/concentration ability after coordinative exercises as compared to normal sport lessons. In a similar vein, Rogge et al () found specific improvements in memory and spatial cognition as a result of a comprehensive balance training, while no effects on executive functions (Stroop task) were observed.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Budde, Voelcker‐Rehage, Pietrabyk‐Kendizorra, Ribeiro, and Tidow (), for example, found better attentional performance/concentration ability after coordinative exercises as compared to normal sport lessons. In a similar vein, Rogge et al () found specific improvements in memory and spatial cognition as a result of a comprehensive balance training, while no effects on executive functions (Stroop task) were observed.…”
mentioning
confidence: 79%
“…Interestingly, intervention effects were only found regarding aerobic performance (6‐min running test), and not with respect to measures involving coordinative abilities (e.g., balancing backwards, jumping sideways). Studies reporting beneficial effects on visuo‐coordinative performance measures typically utilized longer intervention periods (e.g., Graf et al, : 20 months; Rogge et al, : 12 weeks). Thus, while the employed motor coordinative intervention was obviously effective in improving some cardiovascular parameters or general motor fitness, and, as a result, running performance in the 6‐min running test, it was probably too short to unfold beneficial effects also on coordinative performance measures, and thus also on more complex creative performance measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this group presented lower latency values after the induction of AD, which may have occurred because of the influence of external environmental factors such as temperature, noise, or ambient light. 15 The study by Rogge et al 16 demonstrated that 12 weeks of balance training in healthy adults had positive effects on spatial memory and cognition; however, it is still not clear what kind of exercise has better effects on cognition even in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…В связи с положительным влиянием на память, внимание, пространственное восприятие, ряд авторов [23,24], изу чив стимуляцию вестибулярной системы во время физических упражнений по тренировке равновесия и влияние ее на когнитивные функции, среди большого разнообразия так называемых поведенческих вмешательств уделяют особое внимание физическим упражнениям с использованием именно вестибулярной и координационной подготовки. Положительную роль вестибулярной реабилитации в восстановлении когнитивных функций, в том числе зрительно-пространственной ориентации, внимания и исполнительных функций у пациентов с трудноизлечимым головокружением, подтверждают данные одной из недавно опубликованных работ [25], в которой были выявлены корреляционные связи между улучшениями когнитивной функции и переменными, связанными с головокружением и эмоциональным статусом.…”
unclassified